Exploring the potential of stratum corneum biomarkers for assessing psychological distress in health care workers: An observational pilot study - Emal, Lima M.; Tamminga, Sietske J.; Schaafsma, Frederieke G.; Jakasa, Ivone; Peremin, Ines; Kirschbaum, Clemens; Molen, Henk F.; Kezic, Sanja (Health science reports, 2024)
Backgrounds The detection of biomarkers of a stress response in the stratum corneum (SC) could be used as objective assessment of early stress symptoms and monitoring of stress reduction interventions in health care workers (HCWs). Aim The aim of this study is to explore SC biomarkers of immune and hormonal response and skin barrier for assessment of psychological distress (PD) in HCWs. Methods Twenty‐five female HCWs and 25 non‐HCWs participated. SC samples were collected using adhesive tapes at baseline and 3−5 days later (T1). We analyzed 24 biomarkers (immunological, vascular, hormones, and natural moisturizing factors). Stress symptoms were assessed using three scales of Copenhagen Psychosocial Questionnaire. The study involved: identifying SC biomarkers, correlating stress symptoms and biomarkers at baseline and T1, examining stress symptoms between the groups with a Mann‐Whitney test, comparing stress symptoms and biomarkers between groups using Ordinary Least Regression and investigating temporal variability of SC biomarkers at baseline and T1 using a Wilcoxon‐signed rank. Results Fourteen SC biomarkers were identified. We found correlations between general stress and “IL18” (r = 0.55) physical stress and “IL1b” (r = 0.36) and cognitive stress and “MIP3a” (r = 0.38) at baseline and general stress and cortisol (r = −0.49), physical stress and cortisol (r = −0.60) and cortisone (r = −0.67) at T1. We found no differences in stress symptoms and biomarkers between the groups, except for “MIP3a” at baseline. Differences in the biomarker levels between two time points were found for “TARC,” “VEGFA,” “ILRA,” “IL1RA/IL1a,” “NMF,” and “DHEA.” Conclusion The SC can be suitable biological material to assess biomarkers related to immune response, hormonal response, and skin barrier function. The SC biomarkers, showed strong, moderate and weak correlations with stress symptoms. Notably, these associations include cytokines of innate immunity and well‐known stress hormones, cortisol and cortisone.